Adjuvant Potential of Poly-α-l-Glutamine from the Cell Wall of Mycobacterium tuberculosis - Mani, Rajesh (Infect Immun, 2018)
Novel adjuvants are in demand for improving the efficacy of human vaccines. The immunomodulatory properties of Mycobacterium tuberculosis cell wall components have been highlighted in the formulation of complete Freund's adjuvant (CFA). We have explored the adjuvant potential of poly-α-l-glutamine (PLG), a lesser-known constituent of the pathogenic mycobacterial cell wall. Immune parameters indicated that the adjuvant potency of PLG was statistically comparable to that of CFA and better than that of alum in the context of H1 antigen (Ag85B and ESAT-6 fusion). At 1 mg/dose, PLG augmented the immune response of Ag85B, BP26, and protective antigen (PA) by increasing serum antibodies and cytokines in the culture supernatant of antigen-stimulated splenocytes. PLG modulated the humoral response of vaccine candidate ESAT-6, eliciting significantly higher levels of total IgG and isotypes (IgG1, IgG2a, and IgG2b). Additionally, the splenocytes from PLG-adjuvanted mice displayed a robust increase in the Th1-specific gamma interferon, tumor necrosis factor alpha, interleukin-2 (IL-2), Th2-specific IL-6 and IL-10, and Th17-specific IL-17A cytokines upon antigenic stimulation. PLG improved the protective efficacy of ESAT-6 by reducing bacillary load in the lung and spleen as well as granuloma formation, and it helped in maintaining vital health parameters of mice challenged with M. tuberculosis. The median survival time of PLG-adjuvanted mice was 205 days, compared to 146 days for dimethyl-dioctadecyl ammonium bromide-monophosphoryl lipid A (DDA-MPL)-vaccinated groups and 224 days for Mycobacterium bovis BCG-vaccinated groups. PLG enhanced the efficiency of the ESAT-6 vaccine to the level of BCG and better than that of DDA-MPL (P < 0.05), with no ill effect in C57BL/6J mice. Our results propose that PLG is a promising adjuvant candidate for advanced experimentation.